New aspects of pain management in acute and chronic inflammatory syndromes - V. N. Amirdjanova; A. Е. Karateev (Современная ревматология, 2021)
Effective pain control is one of the first and most important challenges in medical practice. Non-steroidal anti-inflammatory drugs (NSAIDs) are the cornerstone of treatment for acute and chronic inflammatory pain syndromes. Of particular interest is a group of patients with a low risk of cardiovascular development and a low to moderate risk of gastrointestinal complications, for whom any NSAID may be recommended. Their choice may depend on the duration and severity of the inflammatory process. The most high analgesic potential have non-selective inhibitors of cyclooxygenase – diclofenac and ketoprofen. Modern technologies give great opportunities for modifying the active substance of NSAIDs and improvement of the drug dosage form in order to hasten their effects and enhance analgesic and anti-inflammatory effect of drugs. In the new form of diclofenac (Dialrapid sachet), sodium salt was replaced by potassium salt, which provided a high rate of both absorption of the active substance and action, comparable to that with intramuscular administration of the drug. It also expanded the possibilities of its use for acute pain and relapses of pain relief in exacerbation of chronic inflammatory diseases. The inclusion of lysine salt significantly changed the pharmacodynamics of ketoprofen. Unlike conventional ketoprofen, its lysine salts (Artrozilen and OKИ) are fast-dissolving compounds with neutral pH that do not irritate the mucous membrane of the gastrointestinal tract, which makes them suitable for long-term treatment of chronic inflammatory pain syndromes.